Internal Quality of Layer Eggs from Traditional Market Majene - W. D. Ningtiyas; A. N. Mukhlisah; S. P. Syah; M. Irfan; S. A. Rab; A. Mutmainna (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
Layer egg is a source of animal protein and food products of animal which popular among the public, and become integral part of consumers’ needs. The high of competitive industry in various countries has caused the quality of the exterior and interior become one of the important assessment indicators. However, there are problems that arise in the process of marketing layer eggs is the quality of egg less attention. Egg quality needs to be maintained; thus, the content remains intact and fresh. This study aimed to determine the quality of Layer eggs from the traditional market Majene.The samples used were 90 layer eggs from traditional market Majene. Sample was was carried out using purposive sampling method with the condition that this location is a place where layer eggs are sold to final consumers such as local people can buy directly without any intermediaries. Parameters based on physical quality include egg weight, albumen index, yolk index and haugh unit value. The data obtained was analyzed qualitative descriptively based on laboratory test results. The results showed that egg weight, albumen index, yolk index and haugh value of eggs from traditional market Majene have good quality and safe for consume based on SNI 2008.